How Review Valence Benefits Umr alence Benefits Umrah Sales P ah Sales Performance: The formance: The Moderating Role of Price - Ishak, Muhamad Izaidi; Harun, Amran (dublin, 2023)
The influence of online consumer reviews on a firm’s sales performance has not yet been investigated in the field of Umrah. In addition, the literature does not explain how price moderates the relationship between online consumer reviews and a firm’s sales performance. Thus, the research objective of this paper is to examine the influence of Umrah online consumer reviews, specifically review valence, on Umrah operator sales performance, with Umrah package price acting as the moderator. 82 Malaysian Umrah operators were involved in this study. The secondary data for Umrah online consumer reviews were collected from Google Maps reviews, which matched Umrah operators’ sales data in 2019. The data were examined using a descriptive analysis followed by multiple regression analysis. The Statistical Package for the Social Sciences software was used to analyse the data. Interestingly, the findings of this study indicate that review valence significantly influences Umrah operator sales performance. Positive and neutral valence positively influences Umrah operator sales performance, whereas negative valence does not. Surprisingly, the moderating effect of Umrah’s package price was not significant. As a result, Umrah operators should work to maintain positive and impartial reviews and continuously monitor negative reviews and respond well to them